2018
DOI: 10.1007/s11783-018-1068-1
|View full text |Cite
|
Sign up to set email alerts
|

Social media and mobility landscape: Uncovering spatial patterns of urban human mobility with multi source data

Abstract: Graphic abstract Highlights: Identify personal activity-specific places based on Weibo data and surveys  Propose ways for detecting and moderating sample bias of Weibo data  Present a graphic representation of urban activity intensity in Beijing, China  Introduce the potential application of Weibo data for urban analysis 2 Abstract: In this paper, we present a three-step methodological framework, including location identification, bias modification, and out-of-sample validation, so as to promote human mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
(63 reference statements)
0
7
1
Order By: Relevance
“…Lee and Son (2018) used text mining methodologies to assess the perceptions of the Taean Coast National Park embedded in text uploaded to the "Taean Travel" blogpost. Cui et al (2018b) studied social media and mobility landscapes with social media data using a three-step methodological framework to uncover the spatial patterns of urban human mobility. It has been shown that social media data are very useful for analyzing various types of content out an expert's point of view, and can be used to analyze various aspects of how people perceive and enjoy landscapes by integrating landscape objects, images and activities.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Son (2018) used text mining methodologies to assess the perceptions of the Taean Coast National Park embedded in text uploaded to the "Taean Travel" blogpost. Cui et al (2018b) studied social media and mobility landscapes with social media data using a three-step methodological framework to uncover the spatial patterns of urban human mobility. It has been shown that social media data are very useful for analyzing various types of content out an expert's point of view, and can be used to analyze various aspects of how people perceive and enjoy landscapes by integrating landscape objects, images and activities.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we observe considerable dissimilarities among the datasets as each source presents unique characteristics. The four selected mobility datasets in this study demonstrate the multifaceted nature of human mobility that has been documented by many (Gonzalez et al, 2008;Cui et al, 2018), and some believe these heterogeneous data sources reflect human mobility from different yet valuable perspectives (Zhang et al, 2014;Lau et al, 2019). Zhang et al (2014) argue that most of the state-of-the-art theory and practice on human mobility focus on single-source data in isolation from one another, inevitably leading to limited representativeness.…”
Section: The Fusion Value In Heterogeneous Mobility Datamentioning
confidence: 92%
“…Yilan et al [36] proposed a three-step methodology. First, in order to find the unique venues, they applied a distance-based clustering algorithm on 'days' of the check-in records instead of the total number of user's check-in.…”
Section: Related Workmentioning
confidence: 99%